National survey on identifying vulnerable workers and availability of occupational health services in the Republic of Macedonia - Jovanka Karadzinska-Bislimovska; J. Minov; Risteska-Kuc, Snezana; S. Stoleski; D. Mijakoski; S. Todorov; Vera Basarovska; Marija Kisman-Hristovska; Teuta Agai-Demjaha (Società italiana di medicina del lavoro, 2010)
In order to identify vulnerable groups and high risk sectors which are at greater need of basic occupational health services, we performed a questionnaire-based study including, as key informants, different stakeholders and key players in the process of improving health and safety at work.
Keywords: health risk; safety at work; questionnaire; vulnerable workers